Postcolonialism, Islamophobia and Inserting Islam Facts in African-American Fiction: Umm Zakiyyah’s If I Should Speak: دراسات ما بعد الكولونيالية، الاسلاموفوبيا وإدراج حقائق الإسلام في الأدب الأمريكي: رواية "لو يجب أن أتكلم" لأم زكية نموذجا - Brioua, Nadira (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2021)
Islam has been growing quickly in the world, yet it is a predominately misunderstood religion. Othering Islam through media propaganda and western writings, and mis associating it with some assumptions are still rampant. Thus, the researcher attempts at showing these assumptions stereotypical prejudgments of Islam and Muslims that are commonly associated with Western assumptions resulted in Islamophobia and exploring the role of counter-discourses in contemporary Black-American Fiction by analyzing Umm Zakiyyah’s If I Should Speak and showing to what extents the novel has an important role in correcting assumptions and narrating the Islamic facts. Thus, this article highlights Umm Zakiyyah’s narrative of Islam’s truth within its historical sources the Qur’an and the Sunnah. The paper analyses Umm Zakiyyah’s reconsideration of Islam’s truth, by focusing on the meaning of Islam and being a Muslim. To do so, this qualitative and non-empirical research is conducted in a descriptive-theoretical analysis, using the selected novel as a primary source and library and online critical materials, such as books and journal articles, as secondary references. Based on the analysis, it is found that Umm Zakiyyah narrates Islam and Muslims to counter the West’s negative view on Islam. Furthermore, based on the story, the power of Muslim self-identification within the historical transparent knowledge based on the Quran’s perspectives leads to the conversion of Tamika Douglass, proving that Islam can be perceived positively by non-Muslims; in this case, it is represented within its subjectivity. It is found that the novel can be a tool of Islamic da’wah [call for the faith]. Hence, the Muslim writers and novelists should write to solve the challenges facing Muslims and the Ummah by Islamizing English fiction. Keywords: Islamophobia, Islamic Postcolonialism, Umm Zakiyyah, fiction, facts. الملخص: يُواجه الإسلام و المسلمين و خاصة الأقليات المقيمة في الغرب عددًا من التحديات، مثل الادعاءات الغربية التي تُمارس ضد الإسلام والمسلمين وتنعكس سلبيًّا لتُنتج مختلف الصور النمطية والتحيزات العنصرية ضدهم سواء باستعمال الميديا أو المنشورات الغربية. وعليه؛ يهتم هذ البحث بتسليط الضوء على هذه التحديات و خاصة الاسلاموفوبيا، و دراسات ما بعد الاستعمار و دور الرواية في تصحيح الشبهات و سرد الحقائق حول الإسلام و المسلمين من خلال اتخاذ رواية "لو يجب أن أتكلم" (2000) للكاتبة أم زكية من الولايات المتحدة الأمريكية. وقد وظَّفت الباحثة المنهج الكيفي غير التجريبي معتمدة على طريقة التحليل الوصفي النظري باستخدام الرواية المختارة كمصدر أوليّ، مع مصادر ثانوية نقدية متوفرة في المكتبة وعلى الشابكة، من مثل الكتب والمقالات الأكاديمية، وبعد التحليل والمناقشة؛ ظهرت أدلة كافية على صراعات عدة تواجه الهوية الإسلامية في الغرب، ممّا يؤدي إلى ضياع هوية المسلم بين الأنا والآخر، فمن جهة ترغب الأنا المسلمة في الحفاظ على جوهرية هوية الأصل، ومن جهة أخرى تتعرض الهوية للضياع والتهجين والازدواجية بسبب السياسات العنصرية والثقافة الغربية والشعور بالتغريب، ومن أهمية هذا البحث. كما أثبتت الدراسة أنّ للرواية دور مهم في تصحيح الشبهات و سرد الحقائق، و لذلك نوصي بأسلمة الرواية و الكتاب بتسليط رواياتهم و أقلامهم على سرد الهوية و الثقافة الإسلامية بدل التقليد و التبعية للأدب الغربي دون مراعاة الهوية و مقوماتها. الكلمات المفتاحية: الاسلاموفوبيا، دراسات ما بعد الكولونيالية و الإسلام، أم زكية، السرد.